Structural and molecular characterization of ligands activating the orphan nuclear receptor Nurr1 (NR4A2) - Ng, Xin Yi (2019)
Parkinson’s Disease (PD), a disease of old age, is the second most common neurodegenerative disease which remains incurable despite many attempts to discover a cure. This study focuses on Nurr1, an orphan nuclear receptor, due to its essential role in the survival and maintenance of dopaminergic neurons in the substantia nigra of the brain. These dopaminergic neurons are usually lost in PD patients, leading to impaired motor functions. Extending from previous studies done by our lab, small molecule ligands were designed to target a plausible co-regulator binding pocket which was unveiled following L1 binding on the ligand binding domain (LBD) of Nurr1. By employing Surface Plasmon Resonance (SPR) and Nuclear Magnetic Resonance (NMR), C3 was identified to bind to the co-regulator binding pocket and is a strong candidate to be chemically-linked to L1, in hopes of increasing its potency as well as its binding affinity and specificity to Nurr1. Moreover, L1 was also identified to increase the expression levels of dopamine-related genes in a LRRK2 G2019S cell-based model. This establishes the potential of L1 as a Nurr1-activating drug and lays the foundation for future development of disease-modifying drugs for PD to prevent or slow down its progression.